Etablering av diplomatiske forbindelser mellom Polen og Norge i årene 1919-1923 - Szymański, Jan (Folia Scandinavica Posnaniensia, 2007)
The paper portrays the process of establishment and, later, development of diplomatic relations between the reborn state of Poland and Norway. The issue of their regulation was discussed by the representatives of both countries at numerous meetings during the peace treaty conference of Paris. As a result of those negotiations, in 1919 Poland opened its mission in Christiania with Czeslaw Pruszyński, envoy extraordinary and minister plenipotentiary, at the helm. The mission of The Kingdom of Norway, established in 1920 in Warsaw, was headed by minister Samuel Eyde. Together with the resumption of diplomatic activity, both governments started work on extension of the network of consular services, which is also presented in the paper.